Adaptation of the Basic Empathy Scale among a portuguese sample of incarcerated juvenile offenders - Pechorro, Pedro Fernandes dos Santos (2015)
The main aim of the present study was to examine the psychometric properties of the Basic Empathy Scale (BES) and of its adapted short version among a forensic sample of incarcerated male juvenile offenders (N = 221). The Portuguese validations of the BES and its adapted short version demonstrated good psychometric properties, namely in terms of the two-factor structure, internal consistency, convergent validity, discriminant validity, and concurrent validity that generally justifies its use among this population. Statistically significant associations were found with callous– unemotional traits and social anxiety. Findings are discussed in terms of the use of the BES and its adapted short version with juvenile offenders.